Real-World Use of Oritavancin for the Treatment of Osteomyelitis - Patrick J. Scoble; Joseph Reilly; Glenn S. Tillotson (Adis, Springer Healthcare, 2020)
Abstract Osteomyelitis is a difficult-to-treat disease that can require both surgical debridement and a prolonged course of antimicrobial therapy. Current standard of care for the antimicrobial treatment of osteomyelitis is fraught with multiple challenges and limitations. Patients typically require the insertion of an indwelling catheter for single or multiple daily intravenous antibiotic infusions for up to 6 weeks. Currently, there are treatment guidelines for only vertebral osteomyelitis, indicating the complexity of the condition. Oritavancin is a long-acting, second-generation lipoglycopeptide, administered intravenously once per week, which has potential to be a useful alternative in the treatment of osteomyelitis. This article reviews occurrence and outcomes of off-label oritavancin use for treatment of osteomyelitis as described in case reports. Analysis included 23 patients treated for osteomyelitis with single- or multiple-dose oritavancin. Overall, clinical cure or improvement was achieved in 87% of patients, and adverse events were mild and reported in only two patients. Clinical efficacy was demonstrated in 81.8% of methicillin-resistant Staphylococcus aureus (MRSA), 71.4% of methicillin-sensitive S. aureus (MSSA), 50% of vancomycin-resistant Enterococcus (VRE), and in the single case of Streptococcus pyogenes. Oritavancin has shown efficacy against Gram-positive pathogens in osteomyelitis, and offers a possible outpatient treatment option for osteomyelitis patients. Future studies are needed to determine dosing frequency in osteomyelitis patients.